IRRIGAÇÃO AUTOMATIZADA NA CULTURA DA COUVE UTILIZANDO SENSOR DE UMIDADE E PLATAFORMA ARDUINO - MARINHO, Guilherme Henrique; SERON, Cassio De Castro; VENDRUSCOLO, Eduardo Pradi; MARTINS, Murilo Battistuzzi; SILVA, Thayná Nascimento Peralta (ANAIS DO ENIC, 2026)
.